Factorize algebraic expressions: (a2 – 5a)2 – 36

Asked by Sakshi | 1 year ago |  77

##### Solution :-

We have,

(a2 – 5a)2 – 36

(a2 – 5a)2 – 62

By using the formula (a2 – b2) = (a+b) (a-b)

(a2 – 5a)2 – 62 = (a2 – 5a + 6) (a2 – 5a – 6)

So now we shall factorize the expression (a2 – 5a + 6)

By considering, p+q = -5 and pq = 6

So we can replace -5a by a -6a

6 by 1 × -6

a2 -5a – 6 = a2 + a – 6a – 6

= a (a + 1) -6(a + 1)

= (a – 6) (a + 1)

So now we shall factorize the expression (a2 – 5a + 6)

By considering, p+q = -5 and pq = -6

So we can replace -5a by -2a -3a

6 by -2 × -3

a2 -5a + 6 = a2 – 2a – 3a + 6

= a (a – 2) -3 (a – 2)

= (a – 3) (a – 2)

∴ (a2 – 5a)2 – 36 = (a2 – 5a + 6) (a2 – 5a – 6)

= (a + 1) (a – 6) (a – 2) (a – 3)

Answered by Aaryan | 1 year ago

### Related Questions

#### Divide as directed (x4 – 81) ÷ (x3 + 3x2 + 9x + 27)

Divide as directed (x4 – 81) ÷ (x3 + 3x2 + 9x + 27)

#### Divide as directed (3x3 – 6x2 – 24x) ÷ (x – 4) (x + 2)

Divide as directed (3x3 – 6x2 – 24x) ÷ (x – 4) (x + 2)

#### Divide as directed 15(y + 3)(y2 – 16) ÷ 5(y2 – y – 12)

Divide as directed 15(y + 3)(y2 – 16) ÷ 5(y2 – y – 12)